Empowerment, Capabilities and Homelessness: The Limitations of Employment-focused Social Enterprises in Addressing Complex Needs. Issue 1 (2nd January 2018) - Tanekenov, Aslan; Fitzpatrick, Suzanne; Johnsen, Sarah
Abstract: 'Empowerment' is often said to be a key objective of policies aiming to improve the lives of homeless people and other vulnerable groups. This paper contends that Sen and Nussbaum's influential 'capability' approach provides an appropriate means of operationalising this arguably nebulous concept. Via a critique of work-focused social enterprises in the homelessness field, as promoted by successive UK governments, it seeks to demonstrate the importance of a multi-dimensional approach to enhancing the capabilities of homeless people with complex support needs. Specifically, it argues for attention to be given to four (independently important) empowerment 'domains': the bodily domain; the political and economic domain; the social and emotional domain; and the creative, intellectual and self-development domain. This broad-based understanding of empowerment implies that a balance must be struck between specialist provision, such as the bespoke social enterprises focused upon in this paper, and more integrative models which seek to support homeless people in ordinary community and workplace settings.